Composition Engineering of All‐Inorganic Perovskite Film for Efficient and Operationally Stable Solar Cells. (2nd June 2020) - Tian, Jingjing; Wang, Jing; Xue, Qifan; Niu, Tianqi; Yan, Lei; Zhu, Zonglong; Li, Ning; Brabec, Christoph J.; Yip, Hin‐Lap; Cao, Yong
Abstract: Cesium‐based inorganic perovskites have recently attracted great research focus due to their excellent optoelectronic properties and thermal stability. However, the operational instability of all‐inorganic perovskites is still a main hindrance for the commercialization. Herein, a facile approach is reported to simultaneously enhance both the efficiency and long‐term stability for all‐inorganic CsPbI2.5 Br0.5 perovskite solar cells via inducing excess lead iodide (PbI2 ) into the precursors. Comprehensive film and device characterizations are conducted to study the influences of excess PbI2 on the crystal quality, passivation effect, charge dynamics, and photovoltaic performance. It is found that excess PbI2 improves the crystallization process, producing high‐quality CsPbI2.5 Br0.5 films with enlarged grain sizes, enhanced crystal orientation, and unchanged phase composition. The residual PbI2 at the grain boundaries also provides a passivation effect, which improves the optoelectronic properties and charge collection property in optimized devices, leading to a power conversion efficiency up to 17.1% with a high open‐circuit voltage of 1.25 V. More importantly, a remarkable long‐term operational stability is also achieved for the optimized CsPbI2.5 Br0.5 solar cells, with less than 24% degradation drop at the maximum power point under continuous illumination for 420 h. Abstract : Operationally stable and high‐efficiency all‐inorganic CsPbI2.5 Br0.5 mixed‐halide perovskite solar cells are achieved for the first time, by introducing the different amount of PbI2 in the all‐inorganic perovskite precursor. The 1.02‐PbI2 devices maintain 76% of their initial efficiency (17.1%) after continuous power output at the maximum power point for 420 h under continuous full‐sun, AM 1.5G illumination (100 mW cm −2 ).